MENINGKATKAN HASIL BELAJAR Pakat DAN GOTONG ROYONG MELALUI MODEL DISCOVERY LEARNING FASE A SD NEGERI LEBO - Herlina Bong (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Herlina Bong. The objectives of this Class Action Research are a). To determine the improvement of learning outcomes through the Discovery Learning model for grade II Phase A students of SD Negeri Lebo. b). To determine the increase in the dimension of mutual assistance through the Discovery Learning model for grade II Phase A students of SD Negeri Lebo. c). To determine the increase in achievement targets through the Discovery Learning model for grade II Phase A students of SD Negeri Lebo. Action Research class consists of 2 cycles, each cycle consists of four stages, namely: planning, implementation, observation and reflection. The subjects of the study were grade II students of SD Negeri Lebo totaling 6 people, consisting of 2 men and 4 women. The object of research is the result of learning and the mutual assistance of students in the study of Catholic Religion and Ethics on the material "The Story of Isaac and Jacob". With data collection techniques are tests, observation and documentation. From the results of the analysis, it was obtained that the learning outcomes and mutual assistance attitudes of students have increased from cycle I to cycle II, that is, for cycle I learning outcomes, no one has entered the proficient category. Many students fall into the category of capable (2 people = 33%) and worthy (4 people = 67%). In cycle II many students fall into the proficient category (4 people = 67%) and proficiency criteria (2 people = 33%), while for the attitude of mutual assistance in cycle I (63.5%) and in cycle II it reaches (89.5%). The conclusion of this study is that the discovery learning model can improve PAKat learning outcomes and phase A mutual cooperation attitudes of SD Negeri Lebo.